التدفــق النفسـي لـدى مستشــاري التوجيـه والإرشـــاد المدرسـي والمهنـي - ضيات جهيدة; بالعيد فتيحة (University Of Eloued جامعة الوادي, 2024)
هدفت هذه الدراسة الحالية إلى التعرف على مستوى التدفق النفسي لدى مستشاري التٌوجيه والإرشاد المدرسي والمهني بولاية الوادي والكشف عن ما إذا كانت هناك فروقاً في مستوى التدفق النفسي لدى أفراد العينة تعزى لمتغير التخصص الأكاديمي، وقد اتبعت الدراسة المنهج الوصفي، وتكونت العينة من(70) مستشار ومستشارة، تم اختيارهم بطريقة المسح الشامل، وقد تم تطبيق مقياس التدفق النفسي لجاكسون ومارش (Jackson & Marsh ، 1996) وأظهرت النتائج وجود مستوى مرتفع من التدفق النفسي لدى أفراد العينة، كما أظهرت النتائج عدم وجود فروق ذات دلالة إحصائية بين متوسطات درجات أفراد العينة في مستوى التدفق النفسي تعزى لمتغير التخصص الأكاديمي، وقد أوصت الدراسة بضرورة إقامة دورات وبرامج لتنمية التدفق النفسي، ونشر ثقافة علم النفس الإيجابي لدى مستشاري التوجيه. The current study aimed to identify the level of psychological flow among school and vocational guidance and counseling counselors in the state of El Oued and to reveal whether there are differences in the level of psychological flow among the sample members due to the academic specialization variable. The study followed the descriptive approach, and the sample consisted of (70) male and female counselors. They were selected using a comprehensive survey method, and the psychological flow scale of Jackson and Marsh (Jackson & Marsh, 1996) was applied. The results showed a high level of psychological flow among the sample members. The results also showed that there were no statistically significant differences between the average scores of the sample members in... The level of psychological flow is due to the variable of academic specialization. The study recommended the necessity of establishing courses and programs to develop psychological flow, and spreading the culture of positive psychology among guidance counselors
دراسة وصفية على عينة من مستشاري التوجيه والإرشاد المدرسي المهني لولاية الوادي
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: التدفق النفسي; Flux psychologique; psychological flow